Polarization-dependent efficient Cherenkov radiation at visible wavelengths in hollow-core photonic crystal fiber cladding - 申向伟 苑金辉 桑新柱 余重秀 饶岚 夏民 韩颖 夏长明 侯蓝田 吴中超 何晓亮 (Chinese physics B, 2013)
Efficient Cherenkov radiation （CR） is experimentally generated by a soliton self-frequency shift （SSFS） in a knot of hollow-core photonic crystal fiber （HC-PCF）. When the angle of the half-wave plate is rotated from 0° to 45°, the Raman soliton shifts from 2227 to 2300 nm, the output power of the CR increases 8.15 times, and the maximum output power ratio of the CR at 556 nm to the residual pump is estimated to be 20：1. The width of the output optical spectrum at visible wavelengths broadens from 25 to 45 nm, and the conversion efficiency of the CR can be above 28%. Moreover, the influences of the pump polarization and wavelength on the CR are studied, and the corresponding nonlinear processes are discussed.